Tindak direktif bahasa Indonesia dalam wacana kelas sekolah dasar - Mudiono, Alif (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study focuses on (1) directive speech acts in Indonesian elementary school classroom discourse and (2) the impact of their use in classroom interaction. The research employed an ethnographic method combined with a pragmatic approach. The results of the data analysis indicate that directive speech acts in elementary school classrooms include ordering, requesting, encouraging, questioning, and directing. Furthermore, the impacts of these directive acts are reflected in students’ responses, such as silence, performing tasks according to the given instructions, and displaying attitudes of willingness and responsiveness toward the learning process.